Revitalizing Heritage: The Role of Urban Morphology in Creating Public Value in China’s Historic Districts - Ruijie Zhang; Miquel Martí Casanovas; Montserrat Bosch González; Sijie Sun (Land)
In the context of historical districts becoming a key to the urban transformation and high-quality development of Chinese cities, this paper investigates the regeneration of historic environments in China, emphasizing the creation of public value through urban morphology. By analyzing five distinct case studies—Chengdu KuanZhai Alley, Shanghai TianZiFang Alley, Guangzhou EnNing Road, Taiyuan ZhongLou Street, and Beijing NanLuoGu Alley—this study explores the relationship between urban form and public value creation from 2000 to 2020. The research posits that the spatial attribute of “public nature” is central to the regeneration process, highlighting the importance of understanding how urban spaces can foster community engagement and social interaction. An evaluation system is constructed to assess the regeneration of historic areas based on spatial “publicness” and people’s perceptions, addressing the need for a more nuanced approach to urban planning. The findings reveal that effective urban regeneration not only preserves historical significance but also enhances the quality of public spaces, thereby contributing to social equity and cultural integrity. This study aims to provide valuable insights for urban planners and policymakers, advocating for a public value-oriented approach to the renewal of historic districts that balances economic development with the preservation of cultural heritage. The integration of public value concepts into heritage management is crucial for creating vibrant urban environments that resonate with community needs and aspirations.